The relationship between food insecurity and overweight/obesity differs by birthplace and length of US residence - Ryan-Ibarra, Suzanne (Public Health Nutr, 2016)
OBJECTIVE: To examine whether the cross-sectional association between food insecurity and overweight/obesity varied according to birthplace and length of residence in the USA among California women. DESIGN: Using cross-sectional, population-based data from the California Women’s Health Survey (CWHS) 2009–2012, we examined whether the association between food insecurity and overweight or obesity varied by birthplace–length of US residence. SETTING: California, USA. SUBJECTS: Women (n 16 008) aged 18 years or older. RESULTS: Among US-born women, very low food security (prevalence ratio (PR)=1·21; 95 % CI 1·11, 1·31) and low food security (PR=1·19; 95 % CI 1·10, 1·28) were significantly associated with higher prevalence of overweight/obesity, after controlling for age, marital status, race/ethnicity, poverty and education. Among immigrant women who lived in the USA for 10 years or longer, very low food security was significantly associated with higher prevalence of overweight/obesity, after controlling for covariates (PR=1·16; 95 % CI 1·07, 1·27). Among immigrant women who had lived in the USA for less than 10 years, low and very low food security were not significantly associated with overweight/obesity, after controlling for covariates. CONCLUSIONS: Food insecurity may be an important pathway through which weight may increase with longer US residence among immigrant women. Public health programmes and policies should focus on increasing food security for all women, including immigrant women, as one strategy to reduce the prevalence of overweight/obesity.